A new cryptic Phyllodonta Warren (Lepidoptera: Geometridae) from Mexico City with documentation of its life history - Garzón-Orduña, Ivonne J.; Brower, Andrew V. Z. (Zootaxa, 2025)
A new species of Phyllodonta is described and illustrated from Mexico: P. coztomatlivora sp. nov. The new species is superficially indistinguishable from others in the so-called latrata species group, from which three other cryptic species from Costa Rica were recently described. However, it differs from them in features of the female genitalia, caterpillar morphology, larval food plant choice and DNA barcode. The new entity may be restricted to high elevations of the Trans Mexican Volcanic Belt; in Mexico City, the species is found inside a protected natural area which should warrant some level of conservation.